Examining green purchasing. The role of environmental concerns, perceptions on climate change, preferences for EU integration, and media exposure - Hlaváček, Martin; Čábelková, Inna; Brož, David; Smutka, Luboš; Prochazka, Petr (Frontiers in Environmental Science, 2023)
Factors impacting green consumption studied in the literature include (1) economic incentives and possibilities, (2) socio-demographic segmentation, (3) values, emotions and personal responsibilities, (4) information including education and mass media, (5) factors related to the locality of the respondents and the lifestyles. While the effects of environmental concerns and perceptions of climate change or green purchasing are well established, the impacts of preferences for EU integration and media exposure are less clear. The article examines the effects of environmental concerns, perceptions of climate change, trust in EU policies, and media exposition on green purchasing employing a representative sample of 904 respondents (aged 15–95 years, M ± SD: 47,74 ± 17,66; 51.40% women, 19,40% with higher education) in the Czech Republic. Methodologically we rely on principal component analysis, correlations, and a set of ordinal regression analyses. The results suggest that (1) the public perceives the agendas of environmental protection and climate change as two different agendas. (2) environment protection attitudes and climate concerns, the acceptance of EU integration positively predict green consumption. (3) the impact of the media exposition proved controversial: printed media and online discussion forums and blogs positively predicted green purchasing, while exposition to online social networks negatively impacted purchasing of organic food; (4) the frequency of watching TV negatively predicted purchasing of environmentally friendly products. We suggest that the advertisements emphasizing low prices may reduce willingness to pay a price premium for green products. It implies that more efforts need to be made on TV and social networks to increase public awareness of green consumption.